Demographic Change and the Labour Share of Income - Torsten Schmidt; Simeon Vosen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Despite similar levels of per capita income, education, and technology the development of labour shares in OECD countries has displayed different patterns since 1960. The paper examines the role of demography in this regard. Employing an overlapping generations model we first examine the mechanisms through which demographic change can affect labour shares. Model simulations show that demographic effects on the labour share are larger in open than in closed economies. Empirical estimates, conducted using panel cointegration techniques for a panel of 18 OECD countries, provide strong support for demographic effects on the labour share. In line with the simulation results, we also find evidence that openness increases this impact.
Keywords: E25; J10; D91; C23; 330; Labour share; demographic change; panel cointegration; Lohnquote; Bevölkerungsökonomie; Overlapping Generations; Offene Volkswirtschaft; Theorie; Schätzung; Bevölkerungsentwicklung; OECD-Staaten